Peluang Dan Tantangan Medical Tourism Dalam Konteks Hukum Di Indonesia - Razy Datuk (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Medical tourism has become a significant global phenomenon in recent years, including in Indonesia. This article examines the opportunities and challenges associated with the medical tourism industry from a legal perspective in Indonesia. With the rapid growth of the healthcare sector in the country, more and more international tourists are seeking high-quality medical care while enjoying tourism attractions. However, amidst promising opportunities, complex legal challenges also arise. This journal outlines the legal framework that regulates medical tourism in Indonesia and analyzes its impact on various aspects, such as health regulations, patient rights, medical responsibilities, and consumer protection. In addition, this article discusses issues such as medical service standards, accreditation of health facilities, and the qualifications of foreign medical personnel entering Indonesia. In this context, legal aspects related to licensing, residence permits, and legal action against questionable medical practices become an important focus. Although medical tourism offers great economic potential, this article also highlights challenges that must be overcome, such as gaps in regulatory implementation, protection of foreign patients, and legal risks for health facilities and medical practitioners. An in-depth analysis of legal opportunities and challenges in medical tourism in Indonesia can provide insight for policy makers, legal practitioners and relevant stakeholders to develop a balanced and sustainable framework for advancing this sector.